2021
DOI: 10.3390/ijerph182111532
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Self-Efficacy as a Mediator in the Reciprocal Relationship between Job Demands and Mental Health Complaints: A Three-Wave Investigation

Abstract: The most recent version of the job demands-resources (JD–R) theory proposes that demanding working conditions and employee strain form a self-perpetuating loss cycle. By acknowledging that such cycles are detrimental for both employees and organizations, the present study aimed to contribute to enhancing the current scarce understanding regarding their explanatory mechanisms. For this purpose, it applied social cognitive theory to propose that occupational self-efficacy mediates the effects of two role stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Sufficient individualized support ( Eurofound, 2022 ), enhancing a feeling of success ( Bandura, 2004 ), must be offered to the worker by the workplace leaders as well as the occupational health service. Even though occupational self-efficacy cannot cure the effects of every adverse job demand, high occupational self-efficacy might decrease perceived stress and promote individual and organizational well-being ( Onyishi et al, 2018 ; Tomas, 2021 ; Galanakis and Tsitouri, 2022 ), thus support the importance of enhancing occupational self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient individualized support ( Eurofound, 2022 ), enhancing a feeling of success ( Bandura, 2004 ), must be offered to the worker by the workplace leaders as well as the occupational health service. Even though occupational self-efficacy cannot cure the effects of every adverse job demand, high occupational self-efficacy might decrease perceived stress and promote individual and organizational well-being ( Onyishi et al, 2018 ; Tomas, 2021 ; Galanakis and Tsitouri, 2022 ), thus support the importance of enhancing occupational self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…People with high occupational self-efficacy have reported higher well-being at work ( Bakker and Demerouti, 2017 ), despite high job demands ( Onyishi et al, 2018 ). Tomas (2021) suggested that by increasing occupational self-efficacy, perceived mental strain might decrease and individual and organizational well-being might be promoted. However, Rigotti et al (2018) found in their study that high job demands, and high strain negatively affected the relationship between career-related self-efficacy and career satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of clarity about the fundamental requirements of the job can be the cause of repeated failures that consistently diminish the employee’s sense of occupational self-efficacy. Ambiguous role circumstances can deter him/her from putting even more effort into the job, effort that can create frustration, anxiety, and fatigue over time ( Acker, 2003 ; Tomas, 2021 ). Role ambiguity negatively affects job performance and can result in job burnout ( McCormack and Cotter, 2013 ; Olivares-Faúndez et al, 2014 ; Wu et al, 2019 ).…”
Section: Role Ambiguitymentioning
confidence: 99%